Comparative population genomics reveals key barriers to dispersal in Southern Ocean penguins. Issue 23 (22nd November 2018) - Clucas, Gemma V.; Younger, Jane L.; Kao, Damian; Emmerson, Louise; Southwell, Colin; Wienecke, Barbara; Rogers, Alex D.; Bost, Charles‐André; Miller, Gary D.; Polito, Michael J.; Lelliott, Patrick; Handley, Jonathan; et al.
Abstract: The mechanisms that determine patterns of species dispersal are important factors in the production and maintenance of biodiversity. Understanding these mechanisms helps to forecast the responses of species to environmental change. Here, we used a comparative framework and genomewide data obtained through RAD‐Seq to compare the patterns of connectivity among breeding colonies for five penguin species with shared ancestry, overlapping distributions and differing ecological niches, allowing an examination of the intrinsic and extrinsic barriers governing dispersal patterns. Our findings show that at‐sea range and oceanography underlie patterns of dispersal in these penguins. The pelagic niche of emperor ( Aptenodytes forsteri ), king ( A. patagonicus ), Adélie ( Pygoscelis adeliae ) and chinstrap ( P. antarctica ) penguins facilitates gene flow over thousands of kilometres. In contrast, the coastal niche of gentoo penguins ( P. papua ) limits dispersal, resulting in population divergences. Oceanographic fronts also act as dispersal barriers to some extent. We recommend that forecasts of extinction risk incorporate dispersal and that management units are defined by at‐sea range and oceanography in species lacking genetic data.